2015
DOI: 10.1001/jamapsychiatry.2015.1054
|View full text |Cite
|
Sign up to set email alerts
|

Shared Predisposition in the Association Between Cannabis Use and Subcortical Brain Structure

Abstract: Prior neuroimaging studies have suggested that alterations in brain structure may be a consequence of cannabis use. Siblings discordant for cannabis use offer an opportunity to use cross-sectional data to disentangle such causal hypotheses from shared effects of genetics and familial environment on brain structure and cannabis use.OBJECTIVES To determine whether cannabis use is associated with differences in brain structure in a large sample of twins/siblings and to examine sibling pairs discordant for cannabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
58
2
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 37 publications
6
58
2
2
Order By: Relevance
“…This is consistent with our previous work suggesting that regionally specific differences between cannabis users and non-users are often inconsistent across studies and that some of the observed associations may actually be related to comorbid alcohol use [40]. The present results are also consistent with a recent study from a large consortium project that found no relationship between cannabis use and cortical GM ( N =466) [68] and a large twin study ( N =483) that found the association between cannabis use and GM volumes was explained by genetics rather than cannabis use [69]. While the analyses reported herein are consistent with the effects reported in studies with large sample sizes, future longitudinal studies will be important to clarify the effects of cannabis and alcohol use on brain structure.…”
Section: Discussionsupporting
confidence: 87%
“…This is consistent with our previous work suggesting that regionally specific differences between cannabis users and non-users are often inconsistent across studies and that some of the observed associations may actually be related to comorbid alcohol use [40]. The present results are also consistent with a recent study from a large consortium project that found no relationship between cannabis use and cortical GM ( N =466) [68] and a large twin study ( N =483) that found the association between cannabis use and GM volumes was explained by genetics rather than cannabis use [69]. While the analyses reported herein are consistent with the effects reported in studies with large sample sizes, future longitudinal studies will be important to clarify the effects of cannabis and alcohol use on brain structure.…”
Section: Discussionsupporting
confidence: 87%
“…However, these negative results may have been due to insufficient power to detect differences with small samples (Block et al, 2000; Jager et al, 2007; DeLisi et al, 2006; Gruber and Yurgelun-Todd, 2005; Medina et al, 2007; Medina et al, 2010). More recent morphological studies with larger samples have found reductions in volume in the anterior and posterior cingulum in patients with heavy use of cannabis and psychosis (Rapp et al, 2013), in the amygdala and hippocampus (Schacht et al, 2012; Cousijn et al, 2012; Gilman et al, 2014; Lorenzetti et al, 2015; Yücel et al, 2008; Pagliaccio et al, 2015), and in the nucleus accumbens (Gilman et al, 2014), along with the medial temporal cortex, temporal pole, parhippocampal gyrus, insula, and orbitofrontal cortex (Battistella et al, 2014, Filbey et al, 2014). Also, functional imaging effects have been reported for regular marihuana users with enhanced cue-elicited craving in the anterior cingulate gyrus, orbitofrontal cortex, and inferior frontal gyrus seen in association with variation in CNR1 SNP rs2023239 (Filbey et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…One recent report found that cannabis use effects were not found when alcohol use was controlled for in statistical analyses (Weiland et al, 2015). In a large study of 483 participants, half of whom were exposed to cannabis, Pagliaccio et al (2015), reported that cannabis exposure was significantly related to reduction in left amygdala (2.3%) and ventral striatal (3.5%) volume. However, the authors interpret their findings as casting doubt on the assumption that cannabis is the causative agent in this volume reduction.…”
Section: Introductionmentioning
confidence: 99%
“…2,4 During periods of abstinence, milder cognitive and psychomotor impairments can persist for weeks in heavy users (average 11 joints per day for 10 years), 5 similar to the extended withdrawal effects seen following the chronic use of other substances. 6,7 Neurobiological differences in brain structure, 8 connectivity, 9 and function 10 have been tentatively identified, though some morphological differences, at least, might reflect pre-existing traits. 8 There is good evidence that cannabis has clinical efficacy for nausea, certain types of pain, and symptoms of multiple sclerosis, 11 but most other proposed indications are largely based on anecdotes, putting physicians in a difficult position (i.e., being asked to prescribe cannabis for conditions where the evidence remains poor).…”
Section: Risks Associated With Cannabis Usementioning
confidence: 99%
“…6,7 Neurobiological differences in brain structure, 8 connectivity, 9 and function 10 have been tentatively identified, though some morphological differences, at least, might reflect pre-existing traits. 8 There is good evidence that cannabis has clinical efficacy for nausea, certain types of pain, and symptoms of multiple sclerosis, 11 but most other proposed indications are largely based on anecdotes, putting physicians in a difficult position (i.e., being asked to prescribe cannabis for conditions where the evidence remains poor). Among the greatest concerns are that cannabis use increases the risk for car accidents 12 and accelerates the onset of -perhaps even precipitates -schizophrenia.…”
Section: Risks Associated With Cannabis Usementioning
confidence: 99%